Association between serotonin transporter gene polymorphism and recurrent aphthous stomatitis - Aastha Manchanda; Asha R Iyengar; Seema Patil (Wolters Kluwer Medknow Publications, 2016)
Background: Anxiety-related traits have been attributed to sequence variability in the genes coding for serotonin transmission in  the brain. Two alleles, termed long (L) and short (S) differing by 44 base pairs, are found in a polymorphism identified in the promoter region of serotonin transporter gene. The presence of the short allele  and SS and LS genotypes is found to be associated with the reduced expression of this gene decreasing the uptake of serotonin in the brain leading to various anxiety-related traits. Recurrent aphthous stomatitis (RAS) is an oral mucosal disease with varied etiology including the presence of stress, anxiety, and genetic influences. The present study aimed to determine this serotonin transporter gene polymorphism in patients with RAS and compare it with normal individuals. Materials and Methods: This study included 20 subjects with various forms of RAS and 20 normal healthy age- and gender-matched individuals. Desquamated oral mucosal cells were collected for DNA extraction and subjected to polymerase chain reaction for studying insertion/deletion in the 5-HTT gene-linked polymorphic region. Cross tabulations followed by Chi-square tests were performed to compare the significance of findings, P < 0.05 was considered statistically significant. Results: The LS genotype was the most common genotype found in the subjects with aphthous stomatitis (60%) and controls (40%). The total percentage of LS and SS genotypes and the frequency of S allele were found to be higher in the subjects with aphthous stomatitis as compared to the control group although a statistically significant correlation could not be established, P = 0.144 and 0.371, respectively. Conclusion: Within the limitations of this study, occurrence of RAS was not found to be associated with polymorphic promoter region in serotonin transporter gene.